Pink-beam serial femtosecond crystallography for accurate structure-factor determination at an X-ray free-electron laser. (2021) - Nass, Karol; Bacellar, Camila; Cirelli, Claudio; Dworkowski, Florian; Gevorkov, Yaroslav; James, Daniel; Johnson, Philip J. M.; Kekilli, Demet; Knopp, Gregor; Martiel, Isabelle; Ozerov, Dmitry; Tolstikova, Alexandra; et al.
No abstract available